Especificación de las condiciones de operación de un biodigestor usando como materia prima estiércol bovino y equino en la finca “Villa Italia” ubicada en el municipio Paipa (Boyacá) (2019)
A proposal was designed for the implementation of a biodigester for the farm "Villa Italia" located in Paipa, Boyacá with bovine and equine excrement, animals that the farm currently has, and that produce about 102 kg of excrement per day, available for the operation of the biodigester. For the realization of the proposal, the chemical characteristics of the excrement were determined to verify its viability to obtain methane gas. Then a pre-experimentation was carried out in which different feed mixtures were compared by varying the amounts of bovine and equine excrement present in the feed to obtain the mixture of excrement with which a greater amount of methane is obtained. From the conditions on the farm two biodigesters were chosen, to be evaluated in an experiment with the mixture of excrement chosen in the pre-experimentation, also evaluating a thermal insulator to obtain as a result the most viable proposal for the farm. A flexible biodigester with its respective financial analysis was finally proposed.